OPTIMALISASI BIAYA DISTRIBUSI DAN ALOKASI PRODUK DENGAN MENGGUNAKAN METODE TRANSPORTASI - Kurnia, Mutiara; Arifin, Jauhari; Sari, Rianita Puspa (Fakultas teknik Universitas Muhammadiyah Jakarta, 2024)
The growth of the manufacturing industry in Indonesia is now increasingly rapid, one of which is in the food and beverage sector. PT. XYZ is one of the beverage industries that has problems, namely the high cost of distribution due to the irregular distribution of distribution from the Factory to the Regional Sales Office (KPW). This study uses the transportation method with the initial solution, namely the Vogell Approximation (VAM) method, the Least Cost, North West Corner (NWC) method and the optimum solution using the Modified Distribution (MODI) method. In addition, a comparison was made with the results of the POM - QM software. The purpose of this research is to optimize distribution costs and allocate distribution of tea products in boxes (tetra pak) with a volume of 250 ml and analyze the optimal distribution costs after the application of transportation methods in distributing 250 ml Sosro Tetra Pak tea products at PT. XYZ. After doing the analysis and calculations, it is concluded that the application of transportation methods using POM - QM software can optimize distribution costs and allocate distribution of 250 ml Sosro Tetra Pak tea products at PT. XYZ. Then After calculating the transportation method, the optimal distribution cost is Rp. 2,059,460,017. There was a decrease in costs of up to Rp. 140,539,983 so the company will save up to 6.39%.